INTRACRYSTALLINE RARE EARTH ELEMENT DISTRIBUTIONS IN APATITE: SURFACE STRUCTURAL INFLUENCES ON INCORPORATION DURING GROWTH - Rakovan J.; Reeder R.J. (My University, 1996)
Intracrystalline REE distributions in fluorapatite have been studied using cathodoluminescence and synchrotron X-ray fluorescence microanalysis (SXRFMA). In the apatite samples studied the {1010} face grows by the spiral mechanism. As a result, polygonized growth hillocks with three vicinal faces occur on {1010}. Face symmetry, m, constrains the [011] and [011] growth steps to be equivalent. However, [001] steps are not symmetry related. REE and Mn cathodoluminescence qualitatively indicates a differential distribution of Mn2+, Sm3+, Eu3+, Dy3+, and Eu2+ between subsectors associated with symmetrically nonequivalent vicinal faces (intrasectoral zoning). SXRFMA shows that the concentrations of all the REEs analyzed (La, Ce, Pr, Nd, Sm, Eu, Gd, Dy, Ho, and Y), except Eu, exhibit a sharp step function, with the change in concentration correlated directly to the boundary between nonequivalent vicinal faces and associated subsectors. Lanthanum, cerium, and praseodymium are enriched in the [001] vicinal subsector, and REEs heavier than Pr, except Eu, are enriched in the <011> vicinal subsectors. The distribution trend observed for Eu may be due to its presence in both the 2+ and 3+ oxidation states.The absence of evidence for anisotropies in step velocity that could influence incorporation supports the proposal of Rakovan and Reeder (1994) that differences in the atomic structure between [001] and <011> steps lead to differential incorporation in apatite. Atomic scale models of the structure of these steps show qualitative differences that are consistent with this proposal. The reversal in the REE partitioning trend between Pr and Nd suggests an ion size effect on the partitioning between nonequivalent steps.The differential distribution of REEs indicates nonequilibrium partitioning. Site specific controls on the partitioning of REEs indicate that partition coefficients can be a function of surface structure and dependent on the spatial segregation of nonequivalent surface sites. Hence, different REE partition coefficients can exist for incorporation at structurally different growth steps.